When the most devastated is in the best position to respond community adaptation after Typhoon Haiyan in Barangay Salvacion, Iloilo - Bracamonte, Nimfa L. (2015)
This research report presents findings from a rapid assessment conducted in December 2013 in a fishing village in Barangay Salvacion, Conceopcion, Iloilo based on key informant interviews and a survey. It describes the effects of Typhoon Haiyan in terms of damage to household properties, livelihood, and a public infrastructure as well as the immediate needs of affected populations a month after the typhoon. The report focuses on Barangay Salvacion's adaptive capacities by examining the ways in which locals have maximized opportunities to rebuild their lives amidst limited resources. Rebuilding, in this sense, is used not only to refer to the construction of shelters and physical facilities but also in terms of developing human knowledge, skills, social relationships, leadership and drawing lessons at the community level. The paper concludes by suggesting the need for a holistic and integrated approach to deal with shared risks, hazards and vulnerabilities, especially among communities affected by Haiyan.
Keywords: Natural disasters; Emergency management -- Iloilo; Super Typhoon Yolanda, 2013